Study of sida yellow spot virus, a begomovirus with a divergent coat protein - Lima, Roberta Rúbia Pinto Nogueira (2022)
Viruses of the genus Begomovirus (family Geminiviridae) are considered one of the most relevant plant pathogens due to the severe losses that they cause in economically important crops. Begomoviruses are transmitted by the whitefly Bemisia tabaci in a persistent- circulative manner, and the only viral protein required for acquisition and transmission by the insect vector is the capsid protein (CP). The CP mediates vector specificity and controls virus transport through the whitefly gut, protecting the virus from degradation, through interaction with a GroEL homologue produced by endosymbiotic bacteria. Although the CP is the most conserved begomovirus protein, we have described a bipartite begomovirus with a highly divergent CP, named Sida yellow spot virus (SiYSV), infecting the non-cultivated plant Sida acuta (Malvaceae). The objectives of this work were to determine whether SiYSV is capable of forming geminate particles, and to carry out the biological and molecular characterization of SiYSV. For the first objective, the 3D structure of the SiYSV CP was predicted using AlphaFold and compared with other typical begomovirus CP's by mTM-align. Then, ultrathin sections of infected plants were observed under a transmission electron microscope for detection of viral particles. Although very different in sequence, the SiYSV CP assumes a 3D conformation similar to that of other begomoviruses. However, particles were not observed under the TEM. For the second objective, the SiYSV host range was assessed, and a whitefly transmission assay was performed. B. tabaci MEAM1 was not able to transmit SiYSV, and an interaction between the CP and GroEL was not observed by BiFC. Furthermore, the subcellular localization of SiYSV-encoded proteins was observed on a confocal microscope and their ability to suppress RNA silencing was analyzed. The results indicate that these proteins had the same pattern of localization expected for typical begomoviruses, but we could not observe any strong silencing suppression activity. Together, these results indicate that the SiYSV-encoded proteins can function just as those of other begomoviruses, thus the possibility that SiYSV forms its capsid cannot be discarded even though we have not yet observed its particles. Also, the inability of B. tabaci to transmit SiYSV may not be related to the inability to form viral particles, but rather to the lack of interaction between CP and GroEL.Keywords: Geminivirus. Coat protein. Bemisia tabaci.